2016
DOI: 10.1111/acer.13251
|View full text |Cite
|
Sign up to set email alerts
|

Tigecycline Reduces Ethanol Intake in Dependent and Nondependent Male and Female C57BL/6J Mice

Abstract: Background The chronic intermittent ethanol (CIE) paradigm is valuable for screening compounds for efficacy to reduce drinking traits related to alcohol use disorder (AUD), as it measures alcohol consumption and preference under physical dependence conditions. Air control treated animals allow simultaneous testing of similarly treated, non-dependent animals. As a consequence, we used CIE to test the hypothesis that tigecycline, a semi-synthetic tetracycline similar to minocycline and doxycycline, would reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…In this commentary, Syapin and colleagues () explore how tigecycline outperforms doxycycline and minocycline in reducing binge alcohol drinking in the dark (DID). In agreement with their findings, Bergeson and colleagues () further elucidate how tigecycline can reliably reduce alcohol dependence in a combined chronic intermittent ethanol (CIE) vapor and 2‐bottle choice alcohol consumption model (Fig. ).…”
Section: Antibiotics and Alcohol Use Disordersupporting
confidence: 69%
See 3 more Smart Citations
“…In this commentary, Syapin and colleagues () explore how tigecycline outperforms doxycycline and minocycline in reducing binge alcohol drinking in the dark (DID). In agreement with their findings, Bergeson and colleagues () further elucidate how tigecycline can reliably reduce alcohol dependence in a combined chronic intermittent ethanol (CIE) vapor and 2‐bottle choice alcohol consumption model (Fig. ).…”
Section: Antibiotics and Alcohol Use Disordersupporting
confidence: 69%
“…Therefore, these results should be strengthened by future studies that test tigecycline on rodent models (i.e., high‐alcohol‐preferring P‐rat or HAD1 rat model) known for their inherent high baseline of alcohol consumption (Bell et al., ). Taken together, Syapin and colleagues () and Bergeson and colleagues () indicate that tigecycline shows significant efficacy in reducing binge alcohol intake as well as alcohol consumption in alcohol‐dependent male and female mice.…”
Section: Antibiotics and Alcohol Use Disordermentioning
confidence: 82%
See 2 more Smart Citations
“…We, and others, have recently shown that treatment with tetracycline analogs reduced alcohol consumption and other alcohol‐mediated responses (Agrawal et al., , ; McIver et al., ), and tetracycline reduction of pain has been well studied since the first evidence was reported in the 1990s (Bastos et al., ). Here, due to our companion studies showing efficacy to reduce binge and dependence drinking as well as alcohol withdrawal symptoms (Bergeson et al., ; Martinez et al., ; Syapin et al., ), we focus on tigecycline (TYGACIL, Pfizer), the first glycylcycline–tetracycline to be approved as an antibiotic by the U.S. Food and Drug Administration (Falagas et al., ). Although some studies have demonstrated effective properties of minocycline (second‐generation semisynthetic tetracycline derivative) in the formalin (Cho et al., ) and surgically‐induced neuropathic pain models (Padi and Kulkarni, ), the novel analgesic properties of tetracycline‐like compounds need to be investigated further, especially if tigecycline, or a derivative, is to become an important AUD treatment.…”
mentioning
confidence: 99%